Loyal Macabebes how the Americans used the Macabebe scouts in the annexation of the Philippines - Flake, Dennis Edward; Juan D. Nepomuceno Center for Kapampangan Studies (Angeles City Juan D. Nepomuceno Center for Kapampangan Studies, Holy Angel University, 2009)
"This book traces the events that convinced the United States government to adopt the practice of pitting one native tribe against another to win their war on foreign soil--a policy that has since defined US involvement in similar wars."--Back cover.
Origins of the use of Macabebe scouts -- The historical role the town of Macabebe played in producing the scouts -- The initial organization of the Macabebe scout -- The effectiveness of the Macabebe scouts -- The transformation of the Macabebe scouts into the Philippine scouts and constabulary -- A summary of the success of using the Macabebe scouts -- Appendix 1. 'A wonderful little black man, this Macabebe' / [by Will Levington Comfort] -- Appendix 2. Rainy season in Pampanga / [by Dennis Flake] -- Appendix 3. Notes on the papers of Matthew A. Batson -- Appendix 4. Excerpts from the full story of Aguinaldo's capture / [by Lazaro Segovia] -- Appendix 5. The story of my capture / [by Emilio Aguinaldo].
Keywords: Pampangan (Philippine people) -- Philippines -- Macabebe -- History; Philippines -- History -- Philippine American War, 1899-1902.; Macabebe (Philippines) -- History, Military